AUTO/BIOGRAPHICAL APPROACHES FOR A POST-CARTESIAN MODEL OF PLURILINGUALISM (Italiano LinguaDue, 2021)
In this article I review some of the trends in auto/biographical research in language education and frame these within the wider context of how ‘education’ and ‘learning’ have been learnt within national systems, and subsequently how knowledge has been constructed as a cognitive enterprise. I argue that, despite conceptual reframing within research-based fields such as sociolinguistics where constructs such as ‘linguistic repertoire’ encourage recognition of fluidity and instability, the Cartesian boundaries fixed between mind and body echo in the tensions between subjective emotions and generalised rationality, and in the compartmentalising of different languages linked to discrete spaces. Using models of inquiry that are increasingly innovative and multi-faceted, auto/biographical work with languages students and teachers opens a space for fruitful deconstruction of these boundaries. Approcci autobiografici per un modello post-cartesiano di plurilinguismoIn questo articolo passo in rassegna alcune delle tendenze della ricerca autobiografica nell’educazione linguistica e le inquadro nel più ampio contesto di come “educazione” e “apprendimento” sono stati appresi all’interno dei sistemi nazionali, e successivamente come la conoscenza è stata costruita come impresa cognitiva. Sostengo che, nonostante la riformulazione concettuale all’interno di campi di ricerca come la sociolinguistica, dove costrutti come “repertorio linguistico” favoriscono il riconoscimento della fluidità e dell’instabilità, i confini cartesiani fissati tra mente e corpo riecheggiano nelle tensioni tra emozioni soggettive e razionalità generalizzata, e nella compartimentazione dei diversi linguaggi legati a spazi discreti. L’utilizzo di modelli di indagine sempre più innovativi e sfaccettati, il lavoro autobiografico con gli studenti e gli insegnanti di lingue apre uno spazio per una proficua decostruzione di questi confini.